COMPARATIVE CHARACTERISTICS OF SOFTWARE SYSTEMS FOR ANALYSIS AND PROCESSING OF SPEECH SIGNALS USING WAVELETS - V. M. Dovgal; Min Zo Hein (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives. This article is devoted to the problem of processing and analysis of speech signals on the basis of the wavelet transform method, which has become one of the most relevant in recent years.Method. The growing relevance and undoubted practical value became the reason for the emergence of a large number of software systems that allow the processing of speech signals on the basis of this method. However, each of these systems has significant differences in the interface provided by the processing tools, functions, has a number of advantages and disadvantages. At the moment, a large number of manuals and recommendations for specific software packages have been written, but these materials are fragmented and unsystematic.Result. This article attempts to systematize the theoretical material and describe the similarities and differences, advantages and disadvantages of the three most popular software systems: 1) MATLAB 6.0/6.1/6.5 Wavelet Toolbox 2/2.1/2.2; 2) Mathcad; 3) Wavelet Explorer of Mathematica.Conclusion. This article will be useful for specialists dealing with the problem of speech signal processing using the wavelet transform method, as it contains material that has practical value, and will allow to facilitate the work of a specialist related to the selection of the optimal for the implementation of a specific task of the software complex.